2021
DOI: 10.3389/fnut.2021.721941
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and Sarcopenia Combined Increases the Risk for Mortality in Older Adults on Hemodialysis

Abstract: Aim: Sarcopenia and malnutrition are highly prevalent in older adults undergoing hemodialysis (HD) and are associated with negative outcomes. This study aimed to evaluate the role of sarcopenia and malnutrition combined on the nutritional markers, quality of life, and survival in a cohort of older adults on chronic HD.Methods: This was an observational, longitudinal, and multicenter study including 170 patients on HD aged >60 years. Nutritional status was assessed by 7-point-subjective global assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
(58 reference statements)
1
16
0
1
Order By: Relevance
“…Our findings showed that a low BMI was strongly associated with sarcopenia in patients on MHD ( P =0.010), consistent with the findings of Macedo et al [ 26 ]. A low BMI often indicates the presence of malnutrition, inadequate energy and protein intake in malnourished patients, gastrointestinal dysfunction, poor digestion and absorption, decreased plasma amino acid concentration, and decreased muscle protein synthesis rate, which, in turn, lead to impaired skeletal muscle quality, strength, and function [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings showed that a low BMI was strongly associated with sarcopenia in patients on MHD ( P =0.010), consistent with the findings of Macedo et al [ 26 ]. A low BMI often indicates the presence of malnutrition, inadequate energy and protein intake in malnourished patients, gastrointestinal dysfunction, poor digestion and absorption, decreased plasma amino acid concentration, and decreased muscle protein synthesis rate, which, in turn, lead to impaired skeletal muscle quality, strength, and function [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…The studies were published between 2014 and 2022 and varied in sample size (33 to 645 patients). Among the included studies, twenty-one studies were conducted in Asian countries (China, Iran, Japan, Korea, Taiwan, Thailand, and Turkey) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], nine in European countries (France, Sweden, Spain, and United Kingdom) [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], eight in South American countries (Brazil and Argentina) [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], two in the USA [ 57 , 58 ], and the remaining one in Australia [ 59 ]. These studies yielded a total sample of five continents (Asia: 45.6%, Europe: 25.9%, North America: 14.3%, South America: 13.7%, and Australia: 0.5%).…”
Section: Resultsmentioning
confidence: 99%
“…These studies yielded a total sample of five continents (Asia: 45.6%, Europe: 25.9%, North America: 14.3%, South America: 13.7%, and Australia: 0.5%). Thirty-one studies [ 19 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 43 , 44 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] were conducted in HD population, seven studies [ 20 , 21 , 28 , 31 , 32 , 42 , 47 ] were performed in PD population, and three studies [ 24 , 33 , 59 ] were carried out in mixed populations (both HD and PD). Of the included patients, the mean age was 62.3 years, 61.4% were male, and 38.6% had diabetes mellitus as a comorbidity with a mean dialysis vintage of 52.4 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper highlights some recent evidence in this regard. Macedo et al investigated the prevalence of malnutrition (7p-SGA), presarcopenia (low muscle strength or low muscle mass) and sarcopenia (low muscle strength and low muscle mass) in 170 older (> 60 years) haemodialysis (HD) patients in Brazil ( [18]. They found that in this group 35.3 were presarcopenic, 14.1 were sarcopenic, and 58.8% were malnourished.…”
Section: Prevalence and Screening/ Assessmentmentioning
confidence: 99%